2020
DOI: 10.4018/978-1-7998-0369-0.ch021
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Technology for Treatment of Pharmaceutical Wastewaters

Abstract: It is estimated 90% of the available water resources will be expended in 15 years and by 2025, nearly 60% of the world population will have scarcity of water if the rate of consumption continues at its present level. The mounting use of pharmaceuticals, with enhanced production, have driven these industrial effluents into so-called emerging pollutants that have become a new environmental problem. Pharmaceutical wastewater, specifically categorized by complex components, are ending up polluting natural water bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Indian pharmaceutical industry is ranked third-largest in the world with reference to volume and is at 14 th position with reference to value. Experiencing 8 to 9 per cent annual growth rate, it is predicted to have 4.5 billion dollars' worth [3] [4] [5]. The pharmaceutical industry encompasses the manufacturing of biological products, botanical products, medicinal chemicals and pharmaceutical products.…”
Section: Introductionmentioning
confidence: 99%
“…Indian pharmaceutical industry is ranked third-largest in the world with reference to volume and is at 14 th position with reference to value. Experiencing 8 to 9 per cent annual growth rate, it is predicted to have 4.5 billion dollars' worth [3] [4] [5]. The pharmaceutical industry encompasses the manufacturing of biological products, botanical products, medicinal chemicals and pharmaceutical products.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofiltration and ultrafiltration are widely used pressure-driven techniques consisting of hallo and sheet-like nanofibers. Many researchers have much-researched cellulose acetate and polymeric materials and their combinations (Konni et al, 2022;Vara et al, 2020). Electrolysis and reversal electrodialysis techniques utilize DC currents bypassing the ions via membranes with oppositely charged materials and found that the ions' rate of flow and concentrations is a deciding factor for filtration efficiencies.…”
Section: Desalinationmentioning
confidence: 99%
“…These techniques are classified based on particle removal into reverse osmosis, membrane filtration, membrane reactor, gas separation, nanofiltration, ultrafiltration, membrane distillation etc. (Vara et al, 2020). Membrane distillation is a thermally driven process to treat water to eliminate the nonvolatile substance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations